Pengaruh Program Keluarga Harapan (PKH) terhadap Kepatuhan Kunjungan Antenatal Care (ANC) pada Ibu Hamil di Pedesaan - Marwasariaty Marwasariaty; Cici Pratiwi; Erma Puspita Sari; Tenny Tarnoto; Rezqiqah Aulia Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: Antenatal Care (ANC) is a crucial effort to reduce maternal and infant mortality. However, in rural areas, pregnant women's compliance with ANC visits remains low. The Family Hope Program (PKH) is a conditional social assistance program that requires pregnant women to undergo prenatal checkups. Objective: This study aims to determine the effect of the Family Hope Program (PKH) on ANC visit compliance among pregnant women in rural areas. Methods: This study used an analytical design with a cross-sectional approach. The sample consisted of 120 pregnant women, both PKH recipients and non-recipients, selected using a purposive sampling technique. The research instruments were questionnaires and KIA (Maternal and Child Health) records. Data analysis was performed using the Chi-Square test and logistic regression. Results: The results showed a significant relationship between PKH participation and ANC visit compliance (p < 0.05). Pregnant women receiving PKH were more compliant with the minimum of four ANC visits as standard compared to pregnant women not receiving PKH. Regression analysis shows that pregnant women receiving the Family Hope Program (PKH) are 2.8 times more likely to be compliant with ANC visits than non-recipients. Conclusion: The Family Hope Program (PKH) has a positive effect on ANC visit compliance among pregnant women in rural areas.